2004
DOI: 10.1029/2003wr002412
|View full text |Cite
|
Sign up to set email alerts
|

A viscoelastic model for groundwater level changes in the Cho‐Shui River alluvial fan after the Chi‐Chi earthquake in Taiwan

Abstract: [1] A viscoelastic model is developed to simulate the groundwater level changes in the Cho-Shui River alluvial fan in Taiwan after the Chi-Chi earthquake. An analytical solution is derived with the assumption that no leakage occurred in confined aquifers during the coseismic period. The solution is used to analyze the data collected from a high-density network of hydrologic monitoring wells in the Cho-Shui River alluvial fan. The simulated groundwater level changes agree with the observations. The viscosity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Few investigators, however, have explored the relation between groundwater fluctuations due to earthquakes and geologic heterogeneity, or exploited the phenomenon for imaging 3‐D hydrologic property heterogeneity in a basin. A recent study by Lin et al [2004], using pore‐elastic and viscoelastic models and field data during the Chi‐Chi earthquakes in Taiwan during 1999, showed that the propagation of groundwater pressure waves induced by earthquakes is indeed influenced by geologic structures and hydrologic heterogeneity. They demonstrated that hydrologic properties of aquifers can be estimated using changes in groundwater levels before and after earthquakes.…”
Section: Data Fusion For Basin‐scale Problemsmentioning
confidence: 99%
“…Few investigators, however, have explored the relation between groundwater fluctuations due to earthquakes and geologic heterogeneity, or exploited the phenomenon for imaging 3‐D hydrologic property heterogeneity in a basin. A recent study by Lin et al [2004], using pore‐elastic and viscoelastic models and field data during the Chi‐Chi earthquakes in Taiwan during 1999, showed that the propagation of groundwater pressure waves induced by earthquakes is indeed influenced by geologic structures and hydrologic heterogeneity. They demonstrated that hydrologic properties of aquifers can be estimated using changes in groundwater levels before and after earthquakes.…”
Section: Data Fusion For Basin‐scale Problemsmentioning
confidence: 99%
“…However, it is difficult or impractical to apply HT to basin-scale aquifer characterization because of ineffectiveness of artificial hydraulic tests for altering groundwater flow fields over kilometers or basin scales. Natural stimuli, such as atmospheric pressure variations [Rojstaczer, 1988], solid earth tides [Hsieh et al, 1988;Rojstaczer and Riley, 1990], ocean tides [Davis et al, 2000;Li et al, 2007b], precipitation [Jan et al, 2013], and even earthquake [Lin et al, 2004], are found to induce groundwater fluctuation from local to regional flow systems. For these reasons, Yeh et al [2008] proposed utilizing natural stimuli as excitation sources for basin-scale hydraulic tomographic surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic wave phenomena in fluid‐containing porous media have received considerable attention in recent years, not only because of their practical importance in reservoir engineering [ Beresnev and Johnson , 1994; Kouznetsov et al , 1998; Seifert et al , 1998; Li et al , 2001] but also because of an increasing scientific awareness of poroelastic behavior in groundwater aquifers [ Schrefler and Zhan , 1991; Wang , 2000; Gambolati et al , 2000; Cosenza et al , 2002; Lin et al , 2004]. A macroscopic theory of wave propagation and attenuation in an isotropic porous medium bearing a single compressible viscous fluid can be formulated quantitatively using the Biot model [ Biot , 1956a, 1956b, 1962; Plona , 1980; Berryman , 1980; Johnson , 1986], wherein two interacting elastic continua are considered.…”
Section: Introductionmentioning
confidence: 99%